Highlights of IFPRI’s recent food policy research for the Asian Development Bank: Reducing poverty and hunger through food policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2012)
In the wake of the food crises of the early 1970s and the resulting World Food Conference of 1974, a group of innovators realized that food security depends not only on crop production, but also on the policies that affect food systems from farm to table. In 1975, the International Food Policy Research Institute (IFPRI) was founded—nine years after the Asian Development Bank (ADB). For the past 38 years, IFPRI has worked to provide solid research and evidence-based policy options to partners in recipient and donor countries and at multilateral agencies. During the same period poverty rates in Asia have fallen by more than half, driven by strong agricultural growth and favorable food policies made possible through the work of, among many others, the CGIAR Consortium, of which IFPRI is a member. However, Asia remains a global hotspot of poverty, with its poorest people concentrated in rural areas where they depend on agriculture for their livelihoods. Asia is also confronting malnutrition, which encompasses the triple burden of undernutrition, micronutrient malnutrition, and obesity. Agriculture and rural development will continue to play a critical role in alleviating poverty and malnutrition in the region—but the issues have changed over time, moving from food subsidies and commercialization of agriculture in the early years to climate change, water, environmental sustainability, value chains, market information systems, and nutrition and health.